Bio-efficacy of Different Bio-pesticides Against Aphid [Myzus persicae (Sulzer)] in Cumin: BIO-EFFICACY OF BIO-PESTICIDES AGAINST CUMIN APHID - Nisha Choudhary; M.M. Kumawat; M.M. Sundria; Krishna Saharan (Annals of Arid Zone, 2024)
A field experiment was undertaken to investigate the effectiveness of certain bio-pesticides against the cumin aphid, Myzus persicae (Sulzer). The study was done on the Gujarat cumin-4 (GC-4) variety, which was cultivated at the Agricultural University, Jodhpur during Rabi, 2020-21. First spray of bio- pesticides was carried out at initiation of pest and second after 20 days. Among the evaluated bio-pesticides, Verticillium lecanii 1.15 WP and Metarhizium anisopliae 1.15 WP were found effective against aphids on cumin. The higher production of cumin seeds as well as net realization was obtained from Verticillium lecanii and Metarhizium anisopliae treated plots against control. However, the standard check (Imidachloprid 17.8 SL) was found most effective which was also reflected in yield as well as in the economics. Among biopesticides Verticillium lecanii 1.15 WP and Metarhizium anisopliae 1.15 WP obtained highest ICBR 1:26.96 and 1:22.40, respectively.